Dialektika antara Komunitas Mata Kita dan Narasi tv dalam Perspektif Strukturasi Giddens - Risky Wahyudi (Jurnal Komunikasi, 2020)
Najwa Sihab is a presenter figure who is idolized by many Indonesian young people. She is known to be brave, decisive and straightforward in conveying his ideas. Her fans also have a community to realize their fandom expressions in Komunitas Mata Kita formed by Narasi TV. The dilemma then is that this community was in fact formed not merely as Najwa Sihab's fandom community, but as a Narasi TV audience. This research examines how the media - in this case streaming-based television - try to create fans and structure them through a political economy perspective. So that we can see how the relationships that occur between the media (Narasi TV), Public Figure (Najwa Shihab), and Fans (Komunitas Mata Kita) in a structure formed by the media.